EXTRACTION AND ATOMIC-ABSORPTION DETERMINATION OF PALLADIUM ON THE BASIS OF THE COMPLEXATION REACTION WITH 2-HYDROXY-5-T-BUTYLPHENOL-4-METHOXY-AZOBENZENE - Pashajanov, Aydin (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Complexation ofPd(II) with 2-hydroxy-5-T-butylphenol-4¢-methoxy-azobenzene(HR) have been researched. The optimum conditions of complex formation and its extraction with chloroform and n-butanol, providing the required fullness of binding of palladium ions were found.Stability constant of the cation complex PdR+ (lgKst=4.3∙1012), and the equilibrium constant of complexation reaction (3.42∙104) were calculated by Komar method. Molar absorption coefficient equals to (4.3±0,1)∙104. The calibration curve was linear at concentrations of palladium 1¸10 mcg / mL.Selective and sensitive technique of extraction-atomic absorption determination of palladium in alloys were developed.